PRESENTASI DIRI JANDA DI SITUS KENCAN ONLINE TINDER : Studi Kasus Pada Pengguna Tinder di Kota Bandung - Estipani Wandasari, - (2019)
This study discusses about self-presentation of widows on Tinder's online dating site. Self-presentation is defined as an attempt to form the image or impression desired by the user to the target. This research was conducted to find out how to use Tinder by widows, to know the widow's self presentation strategy on Tinder and to find out how self-presentation can minimize the stigma of widows on Tinder. The research method used in this research is a case study with a qualitative approach to the widows of Tinder users' online dating sites. The results showed that the motivation of widows to use Tinder was divided into two that is to looking for partners and relationships. The strategy used is Ingratiation and Examplification by providing flattery, using the best photos, using humor, Competence by showing work and education, Intimidation by showing anger and dislike, Supplication by showing sadness. Widows show children on the profile, status and criteria as motivation for self-presentation. The widows try to minimize the stigma by showing anger and showing themselves positively on the Tinder profile with the Intimidation, Ingratiation and Exemplification strategies. Keywords: Widow, Self Presentation, Tinder, Widow Self Presentation Strategy, Online Dating, Stigma, Impression Management